Quality improvement of triage accuracy in the Emergency Department - Adhikari, Sunil; Rijal, Suraj (Journal of General Practice and Emergency Medicine of Nepal, 2020)
Introduction: Triage is the sorting of patients into priority groups according to their need and severity of clinical condition. The study aims to present outcome of complete audit cycle of triage by the triage nurse for quality improvement of triaging in Emergency.Method: 150 patients were randomly selected over 2 weeks who were triaged by the Emergency triage nurse into Emergency (Red), Priority (Yellow) and Queue (Green) in the Emergency Department at Patan Hospital. We followed the WHO quick check triage and assessed those who were accurately triaged, over triaged and those who were under triaged.The necessary changes were done after analysis of data from first cycle and same process was repeated for second cycle. In the second cycle, 150 patients were selected randomly over 2 weeks who were triaged by the Emergency triage nurse. Plan-Do-Study-Act (PDSA) cycle was used for quality improvement cycle.Result: Data were collected from 150 patients in the first cycle and 150 patients in the second cycle. In the first cycle, 48.7 % of patients were correctly triaged, 48.7% were over triaged and 2.7% were under triaged. After the second PDSA cycle, it was found that 65.3% of patients were correctly triaged, 33.3 % were over triaged and 1.3% were under triaged.Conclusion: Accuracy of triage can be improved by continuous quality improvement audit and necessary interventions. Plan-Do-Study-Act (PDSA) cycle is a useful tool for quick detection of problems and acting on necessary interventions for improvement.